Regeneration of deposits of hydrocarbon fields of Ukraine - Lazaruk, Yaroslav (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. In the world's oil and gas-bearing basins, there are known examples of an increase in the reserves of hydrocarbon deposits as a result of inflow of fluids from the deep subsoil. Recently, the theory of the Earth degassing is gaining popularity. There are more and more arguments in favor of the fact that in many oil- and gas-bearing provinces of the world, oil and gas deposits are constantly replenished due to the migration of hydrocarbons through degassing pipes. Certain prospects for maintaining oil and gas production are possible as a result of the natural recovery of depleted deposits in Ukraine as well. However, this issue has not been sufficiently studied and requires further research.The purpose of the article is to argue with actual materials for the regeneration of hydrocarbon deposits, to estimate the probable volumes of their replenishment, to determine the methods of geological research to outline the zones of nourishment of hydrocarbon deposits.Materials and methods. Research materials are actual materials from the development and permanent assessment of hydrocarbon reserves of Ukrainian deposits. The research methodology consists in the analysis of the facts of the replenishment of hydrocarbon deposits from the point of view of new scientific concepts of the supply of hydrocarbons from the deep subsoil.Results. Based on the results of the increase in reservoir pressures of spent gas condensate deposits and repeated calculations of hydrocarbon reserves of the Shebelynka, Chornukhy, Bilousivka and Proletarka deposits of the Dnipro-Donets Basin, a conclusion was made about the replenishment of deposits due to the vertical migration of oil and gas, the probable scales of deposit regeneration were estimated. The results of industrial development of the East Kazantyp and North Bulganak gas fields of the Indolo-Kuban depression also testify to their probable feeding from the depths. Adiabatic fracture formation associated with seismotectonic impulses and phenomena of natural rupture of rocks by deep fluids plays a significant role in the formation of unconventional deposits. The result of fluid fracturing of rocks is specific matrix microcracking. It is well manifested in well cores from depths of more than 5.5 km (Semyrenky, Machushy deposits of the Dnipro-Donets Basin). Hydrocarbon deposits at these depths have a zonal character and are not controlled by the structural factor.Scientific novelty, practical significance and recommendations. Actual materials have proven that some hydrocarbon deposits in Ukraine are constantly being replenished as a result of seepage of deep fluids. It is likely that the main channels of hydrocarbon supply to deposits are deep faults. To determine the degassing channels it is advisable to use the methods of field geophysics and geochemical studies. We can state that the replenishment of gas reserves of some Dnipro-Donets Basin fields according to confirmed facts ranges from 14 to 1800 million m3 annually. It is necessary to monitor the spent deposits, therefore it is advisable not to liquidate decommissioned wells, but to preserve them or transfer to the fund of observation wells, periodically measuring reservoir pressures and determining the character of fluid saturation of spent deposits. It is necessary to manage the process of extraction of hydrocarbons, applying a policy of balanced economical production.